Pembuatan Biofuel dengan Proses Pirolisis Berbahan Baku Plastik Low Density Polyethylene (LDPE) pada Suhu 250 °C dan 300 °C - R. Soelarso Pani; Heribertus Sukarjo; Yustinus Sigit Purwono (Jurnal Engine: Energi, Manufaktur, dan Material, 2017)
The level of fuels’ consumption as an energy source in the world is currently experiencing huge increase. When the use of the oil as fuels is not managed properly, it can be sure that the oil will run out and triggered the world’s energy crisis. Currently, plastik waste become a serious problem that can lead into the environment contamination if not properly managed. One of the solution to overcome the energy crisis and environmental polution is to find and create a renewable energy such as biofuel. The research was conducted in order to know the effect of combustion temperature on pyrolisis process based on the Low Density Polythylene (LPDE) plastic material to produce biofuel. The eraly stages of the research was start with pyrolisis process of the LDPE plastic which comes from the bottle and glass logo waste with the reactor temperature of 250 ºC and 300 ºC. The weight of each material was 2 kg. After getting the crude oil, the researcher examined the crude oil characteristic from pyrolisis process using viscosity test, density test, caloric value test, and flash point test. From the test results, the test results that the gigher the temperature in the pyrolisis reactor, the production of the biofuel oil from pyrolisis were more and have a better quality. The result of the experiment pointed out that the higher the pirolysis reactor temperature , the greater the yield and the better quality. The pyrolisis result was crude oil with each of the weight was 240 ml on the 250 ºC reactor temperature and 260 ml on the 300 ºC reactor temperature. The viscosity test showed the results 3.128 mm²/s on the 250 ºC reactor temperature and 2.698 mm²/s on the 300 ºC reactor temperature. The density on the 250 ºC reactor temperature was 0.9984 and 0.9085 on the 300 ºC reactor temperature. The caloric value test on the 250 ºC reactor temperature showed the results 9084.101 kal/g on the first test and 8765.253 kal/g on the second test. Whereas the caloric value test on the 300 ºC reactor temperature were 9588.312 kal/g on the first test and 9507.779 on the second test. The results of the crude oil flash point test on 250 ºC and 300 ºC showed the same temperature result at 28.5 ºC. From the characteristic test results it can be concluded that the crude oil from the pyrolisis process has approaching the kerosene characteristic and entered into the fuel category.